Ar + Ion Scattering Simulations with a Blue Phosphorus Surface at Small Incidence Angles (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this paper, characteristic trajectories and energy distributions of scattered Ar + ions from the surface of blue phosphorus with the initial energy E 0 = 1 keV and grazing angles = 30 , 50 and 70 are discussed . It is shown that at small values of the incidence angle of bombarding ions, the shape of the surface semichannel ( armchair shape ) can be determined. The scattering coefficient and energy of scattered ions are calculated for the scattered ions. The calculated energy distributions of the scattered ions are analyzed. It is found that the peak of scattered ions from the surface atomic row and the bottom of the semichannel merge and the peak of scattered ions from the bottom of the semichannel is located in the low energy part of the peak.